OPTIMASI PEMBUATAN KRISTAL ETIL DIKLOFENAK DAN KO-KRISTALNYA DENGAN SENYAWA ASAL SERTA UJI STABILITAS - Amalia Darusman, Aisyah
The previous research has found a novel cocrystal from diclofenac acid (DA) and ethyl diclofenac (ED), but the new phase produced was not homogenous and in good purity. This research aimed to retrieve purer cocrystal, beginning through optimization of the ED production, continuing with the choice of the method of making its crystal with DA. Next, the stabilization test is carried out on the cocrystal form. The ethyl diclofenac production produced the purer crystal than the previous by increasing the temperature and time needed for the esterification reaction. The result of thermal analysis showed that the melting point of ED was 67 –68.2 o C. Next, it attempted DA- ED cocrystal formation by a combination of methods: solvent drop grinding (SDG), microwave (MW), and recrystallization with the organic solvents. Besides, co-crystallization was carried out by the reflux method. Solid analysis characterized DA-ED cocrystal by thermal analysis (electrothermal and DSC), vibration spectrophotometry (FTIR), and PXRD. Those instruments proved that recrystallization with acetone and ethanol 96% can yield the cocrystal targeted. The proof of the previous statement was new peak formation at 2?= 16.42 o , 21.26 o , and 33.20 o through PXRD analysis. However, there are still several peaks of origin compound which indicate that the result was not pure. These result was supported by the formation of three peaks of the DSC thermogram, and a wide melting point range (101 o C –152.2 o C). Furthermore, the reflux method with ethanol 96% produced DA-ED cocrystal that was pure with a single DSC endothermic peak and narrow melting range (102.3 –104 o C). The diffractogram also showed that there are no peaks of the original compound. Next, heating using a microwave (power = 199.5W) and humidity (RH 84%/ 25 o C) stability test were carried out on DA-ED cocrystal. Data showed that DA-ED cocrystal produced by the reflux method was stable under these conditions, which does not return to the physical mixture form, and are more resistant to water adsorption. Therefore, it can be concluded that the reflux method produced pure and stable DA-ED cocrystal.